Proceedings of the Brazilian Academy of Dentistry Sponsored Symposium on New Perspectives on Dental Education—9/24/2021 - Vieira, Alexandre R. (Frontiers in Education, 2022)
To create a forum to facilitate further discussion, the Brazilian Academy of Dentistry organized an international symposium to discuss the experience of having to deal with dental education during the implementation of public health measures to mitigate the spread of SARS-CoV-2 in schools in Brazil, India, Portugal, Sweden, and the US. An additional goal of the symposium was to discuss the need of continued faculty development. Therefore, the aim of this paper is to summarize these discussions.